The efficacy of sequential therapy with docetaxel and cabazitaxel for castration‐resistant prostate cancer: A retrospective multi‐institutional study in Japan. (14th November 2022) - Terada, Naoki; Sawada, Atsuro; Kawanishi, Hiroaki; Fujimoto, Takeru; Magaribuchi, Toshihiro; Chihara, Ichiro; Hashimoto, Kohei; Sakurai, Toshihiko; Shimizu, Yosuke; Uegaki, Masayuki; Nakashima, Masakazu; Narita, Shintaro; et al.
Abstract : Objective: This study investigated the efficacy of docetaxel (DOC) and cabazitaxel (CBZ) and examined the factors associated with the prognosis of patients with castration‐resistant prostate cancer (CRPC) receiving DOC‐CBZ sequential treatment in Japanese real‐world data. Methods: We retrospectively evaluated data for 146 patients who received DOC followed by CBZ. The correlations of prostate specific antigen (PSA) decrease rate and time to progression between DOC and CBZ treatment were examined. Combined progression‐free survival (PFS) of DOC‐CBZ and overall survival (OS) from the initiation of DOC and the diagnosis of CRPC were evaluated and compared between patients with high and low PSA levels at the start of DOC and CBZ treatment. Results: No correlations of PSA decrease rate and time to progression were observed between DOC and CBZ. The patients for whom DOC was started in higher PSA levels had significantly shorter combined PFS ( p  = 0.003) and OS from the initiation of DOC ( p  = 0.002). In patients who started DOC at high PSA levels, those who switched to CBZ at low PSA levels had longer OS than those who switched at high PSA levels ( p  = 0.048). The OS from CRPC of patients who started DOC at low PSA levels was significantly longer than those that started at high PSA levels ( p  = 0.030). Conclusions: For patients for whom DOC was not effective, sequential CBZ might have change to be effective. The PSA levels at the start of DOC and CBZ might be a potential prognostic biomarker.